2017
DOI: 10.1039/c7ta08407b
|View full text |Cite
|
Sign up to set email alerts
|

Intermetallic Pd3Pb nanowire networks boost ethanol oxidation and oxygen reduction reactions with significantly improved methanol tolerance

Abstract: Intermetallic nanocrystals are currently receiving extensive attention due to their well-defined crystal structures, highly ordered atomic distribution and superior structural stability that endow them with optimized catalytic activities, stabilities and high selectivity for use as electrocatalysts for fuel cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 65 publications
0
57
0
Order By: Relevance
“…Recently, we reported that the ORR activity of Pd-M (M = Ni, Co, and Fe), prepared by electrochemical potential cycles, was higher than that of Pd after 1500 cycles because the d-band center value of Pd-M was reduced relative to pure Pd, based on hard X-ray photoemission spectroscopy and computational calculations [73]. Several researchers have also reported that ordered intermetallic Pd3Pb has significantly increased electrocatalytic activity for ORR in alkaline media [8,[74][75][76][77]. Electrocatalytic activity over intermetallic Pd3Pb strongly depends on the nanoparticle morphology.…”
Section: Orr On Pd-based Catalysts In Alkaline Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported that the ORR activity of Pd-M (M = Ni, Co, and Fe), prepared by electrochemical potential cycles, was higher than that of Pd after 1500 cycles because the d-band center value of Pd-M was reduced relative to pure Pd, based on hard X-ray photoemission spectroscopy and computational calculations [73]. Several researchers have also reported that ordered intermetallic Pd3Pb has significantly increased electrocatalytic activity for ORR in alkaline media [8,[74][75][76][77]. Electrocatalytic activity over intermetallic Pd3Pb strongly depends on the nanoparticle morphology.…”
Section: Orr On Pd-based Catalysts In Alkaline Mediamentioning
confidence: 99%
“…With the exception of Pt, Pd exhibits the highest electrocatalytic activity (among pure metals) towards hydrogen evolution reactions and ORR. In addition, the ORR kinetics of Pd-based electrocatalysts are not significantly affected by methanol because of their high tolerance to methanol under acidic conditions [7][8][9]. While Pd is currently more expensive than Pt (Pd: 1232.5 USD/ozt and Pt: 796.66 USD/ozt on 5th December 2018), the prices of precious metals fluctuate by nature.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a limiting number of reports considering this possibility, probably because alloying and metal‐ligand interfacial bonding effect have similar purpose. In some reports, alloys are protected by diverse molecules, or polymers, but without studying their effects on the electrocatalytic performance, even if these stabilizing ligands may have an impact as described in this review. While one work describes a negative effect of ligand coordination on Pt−Ni nanoparticles shaping that leads to lower ORR activity, some examples show the synergy between alloying and metal‐ligand interfacial bonding effect for increasing the catalysts’ performance.…”
Section: Chemical Functionalization Of Alloysmentioning
confidence: 99%
“…The Tafel slope calculated for Pd 3 Fe 0.5 Cu 0.5 /C in the high potential range ( i. e., −3.9 V to −2.5 V) is 70.35 mV dec −1 , while the other in the low potential range is 311.93 mV dec −1 . The two Tafel slopes indicates different ORR behaviours in different potential ranges . These two slopes are comparatively smaller than those of Pt/C (84 and 443.4 mV dec −1 ), Pd/C (92.38 and 603.2 mV dec −1 ) as well as for other catalysts compositions and follows the order: Pd 3 Fe/C (72 and 348.66 mV dec −1 )<PdFe/C (74.59 and 373.17 mV dec −1 )<PdFe 3 /C (78.92 and 393.74 mV dec −1 )<Pt/C (84 and 443.4 mV dec −1 )>Pd/C (92.38 and 603.2 mV dec −1 ), in the high and low potential range, respectively.…”
Section: Resultsmentioning
confidence: 99%